Roger L'Estrange and the print culture of the Restoration. - Turner, Dorothy. (University of Ottawa (Canada), 1996)
Roger L'Estrange (1616-1704) is usually characterized either as censor or propagandist, as Surveyor of the Press or as factional polemicist, as discourager or participant in the Restoration booktrades. In fact L'Estrange's career manifests a tension between the desire to control the proliferation of printed texts in public life and the urge to partake in the expanding print culture of the Restoration. L'Estrange's engagement with the booktrades ranged from his early work as anti-parliamentary propagandist (1659-1660) through his career as state-sanctioned Surveyor (1663-1679) to his passionate defences of Stuart absolutism during the Popish Plot and his late work as translator after the Revolution of 1688-89. The seventeenth century witnessed the rising influence of print media in many aspects of political and social life. This dissertation traces L'Estrange's contribution to contemporary political discourse, as well as his engagements with a variety of Restoration booksellers and writers, and his place within a larger rhetorical tradition. In each of these areas, L'Estrange's contributions were shaped by the tensions between his private interests and larger issues of allegiance and duty. Changing subject-sovereign relations, expanding professional opportunities for writers, and increasing public access to printed texts all encouraged and guided L'Estrange's career. As L'Estrange's career was influenced by the cultural forces that surrounded him, so it played an important role in the formation of the complex code of literary-social relations which characterized the turn of the eighteenth century.
Keywords: Biography.